Microbiological characteristics of Pacific shrimp (Pandalus jordani). - Lee, J S (1977)
Microorganisms associated with Pacific shrimp (Pandalus jordani) were isolated and identified. Those on the iced raw shrimp, which yielded an average count of 1.6 x 10(6), were predominantly Moraxella, Pseudomonas, Acinetobacter, Arthrobacter, and Flavobacterium-Cytophaga spp. The blanching and peeling reduced the microbial level to 3.3 x 10(4) and also selectively eliminated Moraxella spp. The microbial flora changed after each processing sequence, and the heat sensitivity and growth characteristics of the representative microbial groups suggested that the presence of Arthrobacter and Acinetobacter spp. in peeled shrimp may indicate inadequate cleaning of raw shrimp or a shorter blanching time. The presence of Moraxella and Flavobacterium-Cytophaga spp. would indicate the degree of secondary contamination, and the presence of Pseudomonas spp. would indicate the shelf-age of the processed shrimp.